Testimonios sobre los hijos: Rosario Ibarra de Piedra, a través de Elena Poniatowska, y Javier Sicilia (Altre Modernità, 2019)
The loss of a child is one of the most unfortunate and inhumane aggressions that has ravaged our social existence in contemporary Mexico, as in other Latin American countries. This tragic situation, however, has resulted in both memorable texts and organizations in civil society to defend human rights and question political system. I will briefly talk about two of these memorable texts. The oldest refers to the loss as disappearance and implies the uncertainty of the whereabouts of the son or daughter. It is titled "Diary of a hunger strike", and recounts the political fasting of a group of mothers of disappeared children, headed by Doña Rosario Ibarra de Piedra, in 1978. This chronicle is included by Elena Poniatowska in one of her best collections, Strong is The Silence (1980). The second text is Javier Sicilia’s novel The Uninhabited (2016), which alludes to certainty of the death of his son. This novel also relates the multiple and contradictory effects that young son’s death produces in the father.